Exclosure of patch of grass at Camp Finney, Wapusk National Park - Bazely, Dawn (1986)
One of the exclosures, made of wooden stakes, rocks, and chicken wire used to section off a specific patch of grass at Camp Finney. Another exclosure can be seen in the background